Antithrombin III Alleviates Myocardial Ischemia/Reperfusion Injury by Inhibiting Excessive Autophagy in a Phosphoinositide 3-Kinase/Akt-Dependent Manner - Kai-yu Huang; Jiao-ni Wang; Ying-ying Zhou; Shao-ze Wu; Shao-ze Wu; Lu-yuan Tao; Lu-yuan Tao; Yang-pei Peng; Jia-qun Que; Yang-jing Xue; Kang-ting Ji (Frontiers Media S.A., 2019)
Autophagy is fundamental to myocardial ischemia/reperfusion (I/R) injury. Antithrombin III (AT) has been shown to protect cardiomyocytes against I/R injury; however, it is unknown whether it modulates autophagy. The objective of this study was to investigate whether AT regulates autophagy during I/R injury and, if so, to identify the potential mechanism involved. Our study showed that AT attenuated I/R injury in vivo and hypoxia/reoxygenation (H/R) injury in vitro. Autophagy was increased both in H9C2 cardiomyocytes during H/R injury and in mouse hearts following I/R injury. The stimulation of autophagy by rapamycin attenuated the protective effect of AT against H9C2 cell injury, indicating that autophagy is involved in the protective role of AT. Furthermore, the cardioprotective effects of AT were abolished by A6730, a specific Akt inhibitor. This study shows that AT exhibits cardioprotective effects by modulating autophagy during I/R injury in a phosphoinositide 3-kinase/Akt-dependent manner.